Food safety hazards in alternative protein-rich plants and seaweeds - Tekiner, H.; Bancalari, E.; Grace, Delia; Acharya, P.; Paciulli, M.; Alinovi, M.; Sogari, G.; Stather, T.; Ennahli, S.; Uçak, S.; Tainsa, M.; Ajal, E.A.; et al. (Global Harmonization Initiative, 2025)
The IPSUS project explores opportunities to extract proteins from upcycled plants, seaweeds, and overlooked sidestreams generated during production or processing stages and to find novel food applications for these new ingredients. Despite a large food safety literature base, a deeper understanding of the safety aspects of various plant and seaweed protein sources is needed. The current study synthesized existing knowledge and gaps on safety hazards associated with brewers' spent grain (BSG), grapes, hazelnuts, potatoes, pumpkins, and seaweeds. A literature review of the last twenty years (2003-2023) was conducted to identify potential microbial, chemical, mycotoxins, heavy metals, and allergenic hazards in focal commodities from production or processing sidestreams using search strings. The records obtained from the PubMed database were exported into an online reference management platform (RMP) and screened by inclusion and exclusion search strings. After removing duplicates, full-text articles were assessed for eligibility by two reviewers. In all, 9127 papers were identified in the PubMed database. After screening based on search strings and removing duplicates by RMP, 1639 articles were left for eligibility assessment. The reviewers finally included 144 articles. Amongst the commodities, most safety studies were on grapes, with 55 papers, followed by potatoes (n=38), seaweeds (n=21), hazelnuts (n=19), pumpkin (n=9), and BSG (n=2). Based on hazard type, heavy metals were the most studied ones, with 49 papers in the final dataset, followed by mycotoxins (n=31), microbial risks (n=23), chemical contaminants (n=21), and allergenic risks (n=20). Overall, to meet the growing need for alternative proteins, their food safety aspects should be extensively studied to deliver safe, healthy, and affordable substitutes based on robust safety standards.